2015
DOI: 10.1017/dmp.2014.88
|View full text |Cite
|
Sign up to set email alerts
|

Networks of Preparedness and Response During Australian H1N1 Outbreak

Abstract: In the context of a disease outbreak in a complex environment and a large geographical area, this investigation has provided a new perspective for understanding how the structure of a collaborative network of personnel affects the performance of the overall network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the context of a pandemic in a complex environment such as a community, a collaborative network has a significant impact on the performance of managing an outbreak. 56,57 Figure 3 illustrates the collaborative network in the community of the Lujiazui.…”
Section: Empowering Volunteer Groups For Emergency Responsementioning
confidence: 99%
“…In the context of a pandemic in a complex environment such as a community, a collaborative network has a significant impact on the performance of managing an outbreak. 56,57 Figure 3 illustrates the collaborative network in the community of the Lujiazui.…”
Section: Empowering Volunteer Groups For Emergency Responsementioning
confidence: 99%
“…Previous studies have emphasized the importance of crosssector coordination in public health emergencies. 6,20 Our analysis suggested that close coordination among health-care organizations and government agencies, not only at the local and state level, but also at the national level, is critical, particularly when an emergency reaches a serious level. However, in doing so, the national health authorities may need to coordinate with provincial/metropolitan and local government authorities first to facilitate such collaboration with hospitals and health-care organizations within each jurisdiction.…”
Section: Discussionmentioning
confidence: 96%
“…A growing number of studies have applied a network approach to the study of interorganisational communication (see, for example, Monge and Contractor, 2003; Shumate and Contractor, 2013; Nohrstedt et al, 2018; O'Connor and Shumate, 2018). Scholars have used network analysis to identify key actors, describe the structures of communication and coordination, and evaluate emergency management performance (see, for example, Choi and Brower, 2006; Hossain et al, 2015). Network analysis allows researchers to scrutinise how organisations build connections with others in their network and their mechanisms of communication and coordination.…”
Section: Literature Reviewmentioning
confidence: 99%